2008
DOI: 10.1007/s12011-008-8137-4
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Different Species of Iodine by Water Spinach and Its Effect to Growth

Abstract: A hydroponic experiment has been carried out to study the influence of iodine species [iodide (I(-)), iodate (IO(-)(3)), and iodoacetic acid (CH(2)ICOO(-))] and concentrations on iodine uptake by water spinach. Results show that low levels of iodine in the nutrient solution can effectively stimulate the growth of biomass of water spinach. When iodine levels in the nutrient solution are from 0 to 1.0 mg/l, increases in iodine levels can linearly augment iodine uptake rate by the leafy vegetables from all three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 9 publications
5
45
0
1
Order By: Relevance
“…The authors also demonstrated that soil extraction with water makes it possible to determine exogenous (synthetic) organo-iodine compounds introduced into the soil with a very good recovery, i.e., L-thyroxine 5-iodocytosine, 7-Iodo-8-hydroxyquinoline-5-sulfonic acid and o-Iodoenzoic acid. Iodoacetic anions (CH 2 ICOOH − ) can be taken up by plants in amounts comparable to or greater than those of I − and IO 3 − (Umaly and Poel 1971;Weng et al 2008). …”
Section: Efficiency Of Iodine Biofortification Of Spinachmentioning
confidence: 99%
“…The authors also demonstrated that soil extraction with water makes it possible to determine exogenous (synthetic) organo-iodine compounds introduced into the soil with a very good recovery, i.e., L-thyroxine 5-iodocytosine, 7-Iodo-8-hydroxyquinoline-5-sulfonic acid and o-Iodoenzoic acid. Iodoacetic anions (CH 2 ICOOH − ) can be taken up by plants in amounts comparable to or greater than those of I − and IO 3 − (Umaly and Poel 1971;Weng et al 2008). …”
Section: Efficiency Of Iodine Biofortification Of Spinachmentioning
confidence: 99%
“…The factors are iodine content in the soil, iodine content in the feed, nutrient consumption and physiological stage of animal As shown in Table 2, soil iodine content was 3.09 mg/kg. Iodine was not classified as essential mineral for plant, but 0.5-1 mg/kg iodine in the soil could stimulate the plant growth (Weng et al, 2008;Landini et al, 2011). Soil iodine content is toxic for plant if the content reaches 10 mg/kg (Umaly and Poel, 1970).…”
Section: Resultsmentioning
confidence: 99%
“…Iodine is not included in essential mineral for plant but 0.5-1 mg/kg iodine in the soil can stimulate forage growth (Weng et al, 2008;Landini et al, 2011). Iodine up to 10 mg/kg in the soil can be toxic for plant (Umaly and Poel, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally it was found that even with these low concentrations there was an increase in biomass (Weng et al, 2008c). Meanwhile Blasco et al (2008) demonstrated that applying iodine concentrations ≤5.1 mg L -1 iodide (I -) in hydroponic lettuce obtained an adequate accumulation of foliar iodine, which was 900 µg -1 g dry tissue, amount that is sufficient to meet the daily demand for iodine intake in humans (150 µg day -1 ) (Charlton et al, 2013) when consumed between 17 and 200 g of fresh tissue of lettuce per week, as this concentration does not exceed the maximum recommended amount which is 2 mg per day.…”
Section: Contenido De Yodo En Las Plantasmentioning
confidence: 99%
“…Adicionalmente se comprobó que inclusive con estas bajas concentraciones se obtuvo un incremento de la biomasa en estas plantas (Weng et al, 2008c). Por su parte Blasco et al (2008) demostraron que aplicando yodo en concentraciones ≤5.1 mg L -1 de yoduro (I -) en lechuga hidropónica se obtuvo una adecuada acumulación de yodo foliar, la cual fue de 900 µg g -1 de tejido seco, cantidad que es suficiente para cumplir la demanda diaria de consumo de yodo en humanos (150 µg día -1 ) (Charlton et al, 2013) cuando se consumen entre 17 y 200 g de tejido fresco de lechuga por semana, ya que esta concentración no excede la máxima cantidad recomendada la cual es de 2 mg por día.…”
Section: Contenido De Yodo En Las Plantasunclassified